Avoiding crowds and reducing mobility is a high risk of Covid-19 incidence in the Working Area of the Paal V Health Center - Adelina Fitri; Emilia Septina; Hendra Dhermawan Sitanggang; Hubaybah; Fitria Eka Putri; Ashar Nuzulul Putra (CV. AFDIFAL MAJU BERKAH, 2022)
The increase in the incidence of COVID-19 has caused quite a bad impact on the whole world in various complex fields. The incidence of COVID-19 cases is high and the case fatality rate (CFR) is high in the world, nationally and in Jambi province and the incidence of COVID-19 cases is high even in Puskemas Paal V also has a fairly high CFR rate. The purpose of this study was to determine risk factors based on the application of health protocols for the occurrence of confirmed cases of COVID-19 in the working area of the Paal V Health Center in Jambi city in 2021. This type of research is analytical and uses a case control study design with a large sample in this study as many as 82 respondents with a ratio of 1:1 so that 41 respondents for the case Group and 41 respondents for the control group using simple random sampling from COVID-19 case data in January-February. It was found that respondents who sometimes avoid crowds (OR: 6.86 95% CI 0.79-59.76) and reduce mobility (OR: 8.24 0.96-70.31) are at high risk of Covid-19. It is necessary to try to keep implementing health protocols while outside the home, especially using masks and limiting official (domestic) travel, especially in groups aged 18-40 years.